Предмет: Алгебра,
автор: dmorozov96
Упростите выражение
Приложения:
Ответы
Автор ответа:
0
5^n*(5^(-1) +5²) / (6*5^n) =
=(1/5+25) /6= 126/(6*5) =21/5 =4,2
=(1/5+25) /6= 126/(6*5) =21/5 =4,2
Автор ответа:
0
1) 5^( n - 1 ) + 5^( n + 2 ) = 5^n • ( ( 1/5) + 25 ) = 5^n • 25,2
2) ( 5^n•25,2 ) : ( 6•5^n ) = 25,2 : 6 = 4,2
Ответ 4,2
2) ( 5^n•25,2 ) : ( 6•5^n ) = 25,2 : 6 = 4,2
Ответ 4,2
Похожие вопросы
Предмет: Українська мова,
автор: viktoriapecarska
Предмет: Українська мова,
автор: enotik804j
Предмет: География,
автор: olgavasilyeva9090
Предмет: Физика,
автор: kote01
Предмет: Математика,
автор: BlackOwlet